Morpho-molecular analysis as a prognostic model for repulsive feedback of the medicinal plant "Andrographis paniculata" to allogamy - Valdiani, Alireza; Talei, Daryush; Javanmard, Arash; Tan, Soon Guan; Abdul Kadir, Mihdzar; Mahmood, Maziah (Elsevier, 2014)
Andrographis paniculata Nees. (AP) is a self-pollinated medicinal herb with a wide range of pharmaceutical properties, facing a low diversity in Malaysia. Cross-pollination of AP accessions leads to considerable rates of heterosis in the agro-morphological characteristics and anticancer phytochemicals of this eminent medicinal herb. However, the poor crossability of the plant at the interpopulation or intraspecific levels is an obstacle from the evolutionary and breeding points of view as an average of 4.56% crossability was recorded for AP in this study. Hence, this research aimed to elicit the impact of parental genetic distances (GDs) on the rate of crossability of AP using seven accessions in 21 possible cross combinations. To this end, a set of 55 randomly amplified polymorphic DNA (RAPD) primers and a total of 13 agro-morphological markers were employed to test the hypothesis. Twenty-two out of the 55 RAPD primers amplified a total of 257 bands of which 107 bands were found to be polymorphic. The principal component analysis (PCA) based on the RAPD markers revealed that the studied AP accessions were distributed to three distinct groups. Furthermore, it was noticed that even a minor increase in GD between two parents can cause a decline in their crossability. Unlike, the morphological-based GDs acted neutrally to crossability. This finding suggests that, despite the low genetic diversity among the Malaysian APs, a population prescreening using RAPD markers would be useful to enhance the rate of fruit set through selecting the genetically adjacent parents.